Strategi Konservasi Lingkungan Berbasis Kearifan Lokal: Studi Kasus Desa Kersik Tuo, Kerinci - Lucky Starada Nova; Maman Rumanta; Rony Marsyal Kunda (Jurnal Nusantara Mengabdi, 2026)
Purpose: This study examines the role of local wisdom in supporting environmental conservation in Kersik Tuo Village, Kayu Aro District, Kerinci Regency, Jambi Province. Research Methodology: A mixed-methods approach was employed, combining qualitative data collection through interviews and participatory observation with quantitative analysis using SWOT and the Analytical Hierarchy Process (AHP). Results: Local wisdom practices, including hunting prohibitions, crop rotation, and communal land management (gotong royong), remain actively practiced in Kersik Tuo Village. However, these practices face pressures from modernization, environmental degradation caused by intensive agriculture, and declining awareness among younger generations. SWOT and AHP analyses identified three priority conservation strategies: strengthening customary institutions, integrating local knowledge with modern science, and enhancing community participation. Conclusions: Local wisdom has significant potential to serve as a foundation for sustainable and adaptive environmental conservation, particularly in responding to contemporary ecological challenges. Limitations: This study is geographically limited to Kersik Tuo Village, which may restrict the generalizability of the findings to other regions with different socio-cultural conditions. Contributions: This study contributes to the development of community-based conservation frameworks by demonstrating the strategic importance of indigenous knowledge systems as a complement to scientific conservation approaches.